2017
DOI: 10.1097/ss.0000000000000216
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biochar, Green Compost, and Vermicompost on the Quality of a Calcareous Soil

Abstract: Purpose: Biochar addition has been recognized as a potential way to improve soil quality. However, questions remain regarding the influence of biochar on soil biological activity. In order to mitigate the possible negative effects of biochar on soil biological activities, it can be enriched by amendments such as compost. Since there is no unanimity on the advantages of biochar when mixed with amendments, it is important to ascertain how the impacts of biochar on soil biological activity could be changed by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 60 publications
3
5
1
Order By: Relevance
“…OMSW-derived BC treatments of 1% and 3% (w/w) increased soil pH from 7.85 to 8.05 and 8.28 for BC300, 8.15 and 8.31 for BC500, and 8.11 and 8.32 for BC700 (Table 4), mainly because of the alkalinity induced by BCs as a result of the basic oxides and carbonates produced during the pyrolytic process. Previous studies have also indicated the application effects of BCs on increasing soil pH [3941]. However, in contrast to our results, other studies have found that alkaline soil pH decreased with biochar addition [14, 18].…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…OMSW-derived BC treatments of 1% and 3% (w/w) increased soil pH from 7.85 to 8.05 and 8.28 for BC300, 8.15 and 8.31 for BC500, and 8.11 and 8.32 for BC700 (Table 4), mainly because of the alkalinity induced by BCs as a result of the basic oxides and carbonates produced during the pyrolytic process. Previous studies have also indicated the application effects of BCs on increasing soil pH [3941]. However, in contrast to our results, other studies have found that alkaline soil pH decreased with biochar addition [14, 18].…”
Section: Resultscontrasting
confidence: 99%
“…The increases in soil pH could have occurred because of the increase in the level of soil exchangeable base cations with BC addition. In a study conducted on calcareous soil, Cardelli et al [39] suggested that the alkalizing effects of BC on soil pH could be explained by the poor buffering capacity of soil induced by the low levels of soil organic matter.…”
Section: Resultsmentioning
confidence: 99%
“…Organic amendments in the amount of a billion tons are added to calcareous soils into the agricultural ecosystem [7] have been reported to increase N soil organic carbon (SOC) to maintain soil fertility and carbon stocks [8]. Compost, vermicompost and biochar incorporation in calcareous soil has positive effects on the biological activity, as reported earlier [9]. Organic amendments, including farmyard manure, green manure [10], humic acid fertilizer and vermicompost improve the physicochemical properties of soil [11].…”
Section: Introductionmentioning
confidence: 79%
“…The occurred increases in soil pH, due to BC application, are mainly because of the alkalinity induced by BCs as a result of the basic oxides and carbonates produced during the pyrolytic process. Previous studies have also indicated the application effects of BCs on increasing soil pH [ 36 38 ]. However, in contrast to our results, other studies have found that alkaline soil pH decreased with biochar addition [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…The increases in soil pH could have occurred because of the increase in the level of soil exchangeable base cations with BC addition. In a study conducted on calcareous soil, Cardelli et al [36] suggested that the alkalizing effects of BC on soil pH could be explained by the poor buffering capacity of soil induced by the low levels of soil organic matter. In this study, the EC values for control soils were 2.03 dS m -1 (CK) and 2.08 dS m -1 (CK +NPK) (Table 4).…”
Section: Biochar Effects On Soil Ph and Ecmentioning
confidence: 99%